FORMULASI PENEGAKAN HUKUM TERHADAP REKSA DANA YANG MELAKUKAN PERBUATAN MELAWAN HUKUM MENURUT HUKUM POSITIF DI INDONESIA - I GUSTI AGUNG WISUDAWAN; AHMAD ZUHAIRI; ADE DIMAN MULADA (GANEC SWARA, 2020)
The development of Mutual Fund Institutions in Indonesia is very rapid, but not without obstacles, the obstacles are in the form of fraudulent practices committed by Mutual Fund managers whether in the form of a company or in the form of a Collective Investment Contract (KIK) led by an Investment Manager (MI), in order to restore investor confidence. Therefore, proper law enforcement formulations are required for Mutual Funds that commit acts against the law according to positive law in Indonesia so that these fraudulent acts can be minimized.The research results show that the formulation of law enforcement against mutual funds that commit acts against the law according to positive law in Indonesia is based on the existence of two theories, namely the System Theory and the Welfare State Theory and Progressive Law. The law enforcement formulations that are carried out are:a. Reformulating in the form of revisions to statutory regulations, especially Law No. 8 of 1995 concerning the Capital Market, because it is considered obsolete and not in accordance with the development of the era which entered the era of free trade and industrial revolution 4.0.b. Strengthening legal sanctions in the revision of Law No. 8 of 1995 on Capital Markets.c. Strengthening the functions and authority of the Financial Services Authority (OJK) as a regulatory, supervisory and supervisory agency in the Capital Market, including strengthening the Investment Alert Task Force.d. Conduct intensive coordination between OJK and other law enforcement officials in order to uncover cases of mutual funds that have committed illegal acts.